Algoritmos de difusão cientes da topologia em redes não infraestruturadas - Lima, Diogo Moutinho Saraiva (2012)
Mobile Ad hoc Networks are wireless networks defined by their lack of supporting infrastructures, where participants can move freely and communicate directly with each other. They are generally composed by devices with lower energy and computation capabilities, and are susceptible to node failure and movement. The interest on these networks has been increasing as they can be used in a widely number of scenarios, like in emergency situations, surveillance, or even in remote locations where it is too expensive to deploy supporting infrastructures. Broadcasting represents the foundation for communication and higher level application development in ad hoc and sensor networks. Therefore, designing broadcasting protocols is a challenging task, as they have to be simultaneously efficient and lightweight. However, broadcast algorithms tend to overlook the importance of the network topology,what may result in efficiency loss in heterogeneous node topologies, specially those where the retransmission of a few nodes is fundamental to ensure the broadcast propagation to large regions of the network. This report proposes a novel broadcasting algorithm that favours the retransmission of the key nodes. Like others approaches, the algorithm uses exclusively the information gathered locally at each node to decide to retransmit, avoiding any control message exchanges or the use of other mechanisms that allow nodes to know their location. Instead, novel interpretations of the information made available by other’s retransmissions allow nodes to make more informed decisions. Simulation results show that, in comparison with other approaches, the algorithm increases the delivery ratio without sacrificing device’s lifetime with an increase in the number of retransmissions.